1978
DOI: 10.1051/jphyscol:19786128
|View full text |Cite
|
Sign up to set email alerts
|

NMR MEASUREMENTS ON LIQUID 3He CONFINED IN ALUMINA AND PLATINUM POWDERS AND GRAFOIL

Abstract: Nous présentons des mesures de la susceptibilité et du temps de relaxation Ti de l' 3 He liquide confiné dans du grafoil, dans de la poudre d'alumine de 400 A et dans de la poudre de platine de 8u. Nous observons une susceptibilité de Curie-Weiss correspondant à une monocouche d'^He adsorbé qui serait responsable du fort taux de relaxation. Ces effets sont supprimés par quelques couches d ,l *He.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The features described in (i) and (ii) agree qualitatively with the observed behavior for TI(T) of Ref. 5. In the case where 4He was introduced to coat the walls, one still finds a small Curie-Weiss contribution to the susceptibility, indicating that part of the high-density fluid 3He is still present.…”
Section: Comparison With the Experimentssupporting
confidence: 77%
“…The features described in (i) and (ii) agree qualitatively with the observed behavior for TI(T) of Ref. 5. In the case where 4He was introduced to coat the walls, one still finds a small Curie-Weiss contribution to the susceptibility, indicating that part of the high-density fluid 3He is still present.…”
Section: Comparison With the Experimentssupporting
confidence: 77%
“…On the other hand, the surface magnetism for various materials filled with liquid 3 He was investigated in the 1970s and the magnetization was found to show a ferromagnetic tendency with Weiss temperature around 0.5 mK. [2][3][4] A very recent study on liquid 3 He magnetization in Grafoil has revealed that the third and the fourth layers grow as solid with increasing the liquid pressure. 5 These upper solid layers show a strong ferromagnetic tendency that depends on the liquid pressure.…”
mentioning
confidence: 98%
“…The introduced 4 He gas corresponds to 2.5 and 3.5 layers of 4 He ͑total 4 He densities of 26.6 and 35.8 nm −2 ͒, respectively, if we use 12.8 and 9.2 nm −2 as the maximum 4 He areal density of graphite for the first layer and the upper layer. Preferentially, adsorbed 4 He was annealed for several hours at 4.2 K. To avoid 4 He desorption, 3 He gas was liquefied slowly at temperatures below 100 mK. The results of 3 He magnetization did not change even after a few months, indicating that the pressure induced solid 3 He layer is expected to reach its equilibrium, owing to its close contact with bulk liquid 3 He.…”
mentioning
confidence: 99%
See 2 more Smart Citations